PREDICTIVE ROLE Of SUPPLIER INNOVATION MANAGEMENT in the PERFORMANCE of MICRO, SMALL and MEDIUM HOTELS in NAIROBI - Munene, Doctor Mary Mwihaki; Mukulu, Professor E. (IJRDO - Journal of Applied Management Science, 2017)
Businesses continue being highly complex due to various reasons such as competition, growth in size, an educated workforce, change in technology amidst other factors, the predictive role of supplier innovation management cannot be denied. This study looks at the various factors that entrepreneurs should concentrate on to achieve success in supplier innovation management. These include supplier relations, supplier involvement and capability, automated systems, and supplier data analysis. Literature was reviewed from various sources of secondary data with the aim of finding out what various scholars have to say about the contribution of supplier innovation management to firm performance. Data was collected by IJRDO-Journal of Applied Management Science ISSN: 2455-9229 Volume-3 | Issue-11 | November,2017 | Paper-4 49 use of exploratory design, through personal interviews on 100 sampled hotels. The data was processed using correlation and multiple regression analysis. The results showed that supplier innovation management had no significant predictive role in the performance of micro, small and medium hotels. The negative results may have need as a result of poor implementation by the Nairobi hotels and travel advisories by various tourist destinations. To be successful in supplier innovation management it was important for hotels to generate proper supplier relationships, be highly professional and ethical and transparent among other factors.